Substandard feeding in children undergoing mechanical ventilation in pediatric intensive care unit: A retrospective cohort study in China - Meng Li; Ying Wang; Qingxiu Chen (Belitung Raya Foundation, Indonesia, 2023)
Background: Enteral nutrition is a common yet vital practice in the pediatric intensive care unit (PICU). However, the status of substandard feeding of enteral nutrition in PICU children undergoing mechanical ventilation remains unclear and can be detrimental to the children’s prognosis. Objective: This study aimed to evaluate the incidence, nursing care status, and influencing factors of substandard feeding in children undergoing mechanical ventilation in the PICU. Methods: This study employed a retrospective cohort design. Children undergoing mechanical ventilation and enteral nutrition in the PICU of a public hospital in China from 1 June 2021 to 31 December 2022 were selected using convenience sampling, and their characteristics were collected and evaluated. Pearson correlation analysis and multivariate logistic regression analysis were conducted to assess the influencing factors of substandard feeding in PICU children with mechanical ventilation. Results: A total of 156 PICU children undergoing mechanical ventilation were included for analysis in this study. The rate of substandard feeding in PICU children was 65.38%. Statistically significant differences were observed in diarrhea, vomiting, the use of sedatives, and average infusion speed between the substandard feeding group and the standard group (p <0.05). Pearson correlation results indicated that diarrhea (r = 0.595), vomiting (r = 0.602), and average infusion speed (r = 0.562) were correlated with substandard feeding and characteristics of included ICU children undergoing mechanical ventilation (p <0.05). Logistic regression results found that diarrhea (OR = 2.183, 95%CI: 1.855 2.742), vomiting (OR = 3.021, 95%CI: 2.256 4.294), and average infusion speed ≤40 mL/h (OR = 2.605, 95%CI: 1.921 3.357) were independent risk factors for substandard feeding in mechanically ventilated children in the ICU (p <0.05). Conclusion: The rate of substandard feeding in children with mechanical ventilation in the PICU was high. Diarrhea, vomiting, and slow infusion speed are important influencing factors for substandard feeding. It is suggested that nurses and other healthcare professionals take targeted measures, including the prevention and care of diarrhea and vomiting, as well as monitoring and adjusting the infusion speed of enteral nutrition, to reduce the occurrence of substandard feeding.